Azedinha (Rumex acetosa L.) : caracterização morfológica, requerimento nutricional e qualidade sensorial - Lima, Maria Angélica Suedan Souza (2015)
Azedinha (Rumex acetosa L.) has pleased the consumer for its sour taste. Considered an unconventional vegetable, their redemption becomes important to allow notable gains from the nutritional, social, cultural, economic and environmental point of view. The objective was to characterize morphologically copies of azedinha obtained from seeds, determine their sensory characteristics and acceptance, as well as analyze some physicochemical parameters, and determine the absorptions of macro and micronutrients and biometric parameters during 60 days after transplanting (DAT). The experiment was conducted at the Centro de Ciências Agrárias, belonging to the Universidade Federal São Carlos - UFSCar in the city of Araras - SP. Biometric parameters were evaluated (length of the leaf, relative leaf area, fresh and dry weight of shoots) and the macro and micronutrients absorption march from plants collected at 15, 20, 25, 30, 35, 40, 50 and 60 DAT. They evaluated the length, width and length / width ratio of leaf blade; petiole length and width close to the blade; diameter of the stump; the shoot length; length of ochreas; shape of the leaf blade; kind of apex; base form; type of veining and type of margin of the leaf blade; type of ochreas; characterization of the stem; length and diameter (neck) of the root. It also determined the levels of ascorbic acid, phenolic compounds and chlorophyll parameter. For sensory analysis was used the Quantitative Descriptive Analysis (QDA). Sensory analysis of acceptance was conducted with 52 judges, in relation to vii appearance, aroma, flavor, texture and overall impression, as well as purchase intent. The biometric parameters increased over time after transplantation and most markedly after the recommended times for harvest (20 and 35 DAT). The maximum levels of macro and micronutrients accumulated in the shoot, in descending order were as follows: K > N > Mg > P and Fe > Mn > Zn > Cu. The morphological descriptors with greater discriminatory power for azedinha were the types of margin and venation of the leaf blade, the characterization of the stem, the presence of ochrea and shape of the leaf blade, ranging from sagittate the hastate. It also infers that the best harvest time is between 20 and 35 DAT. The average content of ascorbic acid was 10,25 mg 100g-1 sample, total phenolic 291,46 mg of gallic acid 100 g-1 dry weight and chlorophyll parameter was 36,6 SPAD units. As for the quantitative descriptive analysis, the leaves of azedinha framed up closer to dark green; most have arrow or spear shape; smooth; with sharp aroma of grape skin; more acid flavor, such as green blackberries; there was no residual bitterness; they were folding; wrinkle free; soft to chew and thin. Regarding the acceptability test, the notes to the variable color, flavor, texture and overall acceptability were high and most judges would buy this vegetable.